2011
DOI: 10.1007/s12032-010-9792-9
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine inhibits cisplatin-induced apoptosis in NCI-H446 cells

Abstract: Nicotine is not only a major component in tobacco but is also a survival agonist that inhibits apoptosis induced by certain agents including chemotherapeutic drugs. Here, we first showed that nicotine inhibits cisplatin-induced apoptosis in NCI-H446 cells. An MTT assay, Annexin V-FITC staining, RT-PCR, and Western blot were applied to identify the viability of cells, stages of apoptosis, mRNA and signaling proteins expression, respectively. First, we observed that nicotine induced no significant apoptosis when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…While tobacco smoke carcinogens initiate tumors, the current literature raises the possibility that nicotine additionally confers a survival advantage to already initiated tumors (28, 57, 65, 66) by promoting cell cycle progression and by preventing apoptosis (66, 67). This is of particular concern in the context of tobacco smoke components conferring resistance to chemotherapeutic drugs (66, 67) as well as radiation (68).…”
Section: Regulation Of Survival Pathways By Nachrs – Anti-apoptotic Ementioning
confidence: 99%
See 2 more Smart Citations
“…While tobacco smoke carcinogens initiate tumors, the current literature raises the possibility that nicotine additionally confers a survival advantage to already initiated tumors (28, 57, 65, 66) by promoting cell cycle progression and by preventing apoptosis (66, 67). This is of particular concern in the context of tobacco smoke components conferring resistance to chemotherapeutic drugs (66, 67) as well as radiation (68).…”
Section: Regulation Of Survival Pathways By Nachrs – Anti-apoptotic Ementioning
confidence: 99%
“…This is of particular concern in the context of tobacco smoke components conferring resistance to chemotherapeutic drugs (66, 67) as well as radiation (68). Multiple studies have reported that patients who smoke demonstrate poor response to cancer chemotherapy, and have worse prognosis than their non-smoking counterparts (65, 69, 70).…”
Section: Regulation Of Survival Pathways By Nachrs – Anti-apoptotic Ementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, about one-third of patients with lung cancer continue to smoke after diagnosis [2], not to mention non-smokers patients with lung cancer exposed to second-hand smoke. Recently, evidence for an increasing treatment-resistance associated with cigarette smoke exposure has been emerging [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…' Because nAChR agonists exert neuroprotective and neurotrophic actions, an important consideration in treating chemotherapy-induced cognitive deficits with specific nAChR agonists is the impact of the agonist on the effectiveness of the chemotherapy. Studies indicate that exposure of cells to nicotine in vitro attenuates the antiproliferative activity of several chemotherapeutic agents, including etoposide, doxorubicin, gemcitabine, cisplatin and taxol [182][183][184][185][186][187][188]. Although nicotine appears to reduce the efficacy of these chemotherapeutic drugs, the specific nAChRs involved in this effect have not been established.…”
Section: Future Directions and Considerationsmentioning
confidence: 99%